Consequences of premature birth on dental health - Vlad Dima; Andreea Calomfirescu-Avramescu; Simona Vladareanu; Andrada Mirea; George Iancu; Valentin Varlas; Roxana Elena Bohiltea (Amaltea Medical Publishing House, 2021)
Preterm infants are a special category of patients known for high rates of associated morbidities. This morbidities range from breathing problems to motor and neurologic impairments. The survival rates are improving along with better neonatal care, but the effects of preterm birth can still be seen in this category in patients. Even though dental health problems are not a largely debated subject, one should take into consideration that teeth, like other tissues are influenced by prematurity, and preterm babies are more likely to develop dental problems.